Analisis Efektivitas Pengendali Biaya Produksi Pada Pt. Daur Ulang Sejahtera (Dsa) Di Bandar Lampung (Study Kasus pada PT Daur Ulang Sejahtera (DSA) di Bandar Lampung) - . Thontowi; . Yeni; Syamsu Rizal (Universitas Bandar Lampung (UBL), 2012)
PT DSA is a company engaged in the industry which produces plastic ore used as the main ingredient manufacture of household appliances. Problems faced by PT DSA are: the presentation of information in terms of ore production cost of plastic, in which top management as users can not report quickly and accurately obtain the required data in decision-making. And the problem is formulated: